Convolutive blind separation algorithm based on complex Givens matrix and bat optimization - Zhi-cheng JIA; Da-wei HAN; Lei CHEN; Yan-ju GUO; Hao-da XU (Tongxin xuebao)
For the limitations such as many unknown parameters, the separation accuracy was easily influenced by initial value of separation matrix in traditional convolutive blind separation, a kind of frequency method based on complex Givens matrix and bat optimization was proposed. The algorithm used a series of complex Givens matrices to denote separation matrix, it reduced unknown parameters, decreased the difficulty and the amount of calculations as a result. Be-sides, the algorithm utilized bat algorithm instead of conventional gradient algorithm to optimize rotation angles and completed the separation of complex linear instantaneous mixing signals at each frequency point, the use of bat algorithm made the optimization ability better. In addition, little prior information was needed and signals following various distri-butions could be separated. Simulation results show that the proposed method can realize convolutive blind separation ef-ficiently.